2020
DOI: 10.1007/s13238-020-00692-z
|View full text |Cite
|
Sign up to set email alerts
|

Electric field-driven building blocks for introducing multiple gradients to hydrogels

Abstract: Gradient biomaterials are considered as preferable matrices for tissue engineering due to better simulation of native tissues. The introduction of gradient cues usually needs special equipment and complex process but is only effective to limited biomaterials. Incorporation of multiple gradients in the hydrogels remains challenges. Here, betasheet rich silk nanofibers (BSNF) were used as building blocks to introduce multiple gradients into different hydrogel systems through the joint action of crosslinking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 47 publications
0
52
0
Order By: Relevance
“…In this work, β-sheet rich silk nanofibers moved to the anode of an applied electric field, with the migration kinetics tuned to the gelation rate Peer reviewed version of the manuscript published in final form in Trends in Biotechnology (2020). of the surrounding polymer (GelMA, N-isopropylacrylamide or amorphous silk nanofiber solution) (Figure 3C) [70].…”
Section: Component Redistributionmentioning
confidence: 99%
“…In this work, β-sheet rich silk nanofibers moved to the anode of an applied electric field, with the migration kinetics tuned to the gelation rate Peer reviewed version of the manuscript published in final form in Trends in Biotechnology (2020). of the surrounding polymer (GelMA, N-isopropylacrylamide or amorphous silk nanofiber solution) (Figure 3C) [70].…”
Section: Component Redistributionmentioning
confidence: 99%
“…In the case of MSCs, for instance, it has been shown that the RGD cell-adhesive motif is essential for stem cell survival at the early stages of 3D culture in PEG hydrogels, while removal of ligands at later stages does not compromise the viability of cells, but rather improves their differentiation (Kloxin et al, 2009 ). To overcome limitations in delivering natural cues in a spatiotemporal manner the development of dynamic biomaterials that allow for reversible modulation of the physicochemical properties and on-demand release of the desired molecules via either cell-mediated or user-mediated mechanisms, represents a promising strategy (Willerth et al, 2008 ; Leijten et al, 2017 ; Schneeberger et al, 2017 ; Cimmino et al, 2018 ; Kratochvil et al, 2019 ; Xu et al, 2020 ). A characteristic example where the delivery of physicochemical cues is mediated by cell activity is remodelable 3D hydrogels.…”
Section: Building Blocks For Developing Human Tissue Equivalentsmentioning
confidence: 99%
“…Between week 8 to 12, newly formed bone was found in the case of the stiffest hydrogel samples, whereas the aligned fiber structure also led to alignment in the new tissue. The fabrication method with two silk fibroin morphologies and electric field alignment was then used by the same group to fabricate gradient hydrogels [ 132 ]. In further detail, horseradish crosslinking times and resulting gradient mechanical properties were investigated.…”
Section: Silk-based Hard Tissue Engineeringmentioning
confidence: 99%